Dance Films Development In Indonesia - Ardianto, Deny Tri (2016)

(untitled)
Dance Film is a film genre which is less recognized by the society. Track record regarding dance film in Indonesia are also difficult to be traced due to its small number, limited documentations, and some perceptions which assume that dance film is the same as dance documentary. Therefore, it is necessary to specify dance film terminology and to review its historical development since the moment of its emergence in early 1900s and up to the present day. Dance film presence is also essential to enrich scientific repertoire in the field of creations, to complement genre development in Indonesian film industry, and to build people’s appreciation in response to the existence of a new mean of narration and language of expression in Indonesian film